Efek Sitotoksik Ekstrak dan Fraksi Umbi Paku Atai Merah (Angiopteris ferox Copel) Terhadap Sel Kanker Payudara T47D: Cytotoxic Effects of Paku Atai Merah (Angiopteris ferox Copel) Tuber Extract and Fractions against T47D Breast Cancer Cells - Aisyah, Andi Nur; Nur, Syamsu; Lukitaningsih, Endang; Rumiyati, Rumiyati; Burhan, Asril; Adjara, Syafia Mustika; Rahim, Kurnia (Universitas Tadulako, 2020)
The use of natural products has been widely used as a resource of new bioactive chemical compounds. One of them is the Paku Atai Merah (Angiopteris ferox Copel) tuber which has long been used empirically by the Dayak tribe of East Kalimantan as an anti-cancer. The purpose of this study was to determine the anticancer cytotoxic activity of the extract and fractions of Paku Atai Merah tuber against T47D breast cancer cells in vitro. Extract of Paku Atai Merah tubers was obtained by maceration method using ethanol solvent until obtained the ethanolic extract then fractionated using various solvents to obtain n-hexane, ethyl acetate, and aqueous-ethanol fractions. The cytotoxic effect was carried out based on the MTT assay. Phytochemical screening tests showed positive results for the presence of flavonoid, phenolic, tannin, saponin and steroid compounds. The results of the cytotoxic activity study showed that the ethyl acetate fraction had moderate cytotoxic activity in T47D cancer cells with an IC50 value of 84.8 µg/ml. Ethanol extract (513.06 µg/ml) and n-Hexane frsction (881.97 µg/ ml) were also included in the weak category. This study indicates that ethyl acetate fraction can be developed as a supportive therapy for breast cancer treatment.